Propriedades de sílicas híbridas obtidas por co-condensação com HDTMS e TPOAC - Ferreira, Aurélia Retiella Oliveira (Universidade Federal de São Carlos, 2016)
The master degree work presented is a result of a research conducted together with a group, which has worked on the modification of the synthesis CTA-MCM-41, that silica belongs to the mesoporous materials family (composed by MCM-41, MCM-48 e MCM- 50). The synthesis of silicas was disclosed by Mobil Oil Corporation in 1992 due to processing of higher molecular that the processed for microporous silica. Between the mesoporous silicas, the more studied it’s MCM-41. When the MCM-41 has in their pores the cation (CTA+) it has also basic catalytic sites due to siloxi anion (≡SiO-) associated. In evaluating the basic character of the CTA-MCM-41 in transesterification reactions of monoester, we obtained satisfactory conversions, but when catalyst reused, there was a loss of catalytic due to leaching cations CTA+. Then, the catalyst loses part of the basicity necessary to that reaction. This work has challenged, synthesize hybrid catalysts that are able of keep the same catalytic activity when reused. From the research, the formation of MCM-41, the cocondensation of TEOS with functionalized groups can result in new hybrid materials. These materials offer functional groups connected to wall silica, [Si]– CnH(2n+1), this connection type can create more stability to this form of silica. For this particular research, arose the proposal to use together with TEOS, the hexadecyltrimethoxysilane (silane) or dimethyloctadecyl[3-(trimethoxysilyl) propyl] ammonium chloride (silônio) like fonts of silicas in the synthesis of the MCM-41. The silicas synthesized showed X-ray diffraction characteristic of the MCM-41 and the presence of the silane and the silônio was proven through the technique nuclear magnetic resonance of 29Si and of the termogravimetric analysis. The silicas were evaluated catalytically by transesterification reaction of ethyl acetate in methyl acetate and ethanol. The conversions obtained in the reaction, when compared with the silica synthesized just with TEOS, were lower, due to deposition silônio group on silica surface, hindering the access to basic sites.
Keywords: Peneiras moleculares; Co-condensação; Transesterificação; Molecular sieves; Co-condensation; Transesterification; ENGENHARIAS::ENGENHARIA QUIMICA